2014
DOI: 10.1111/2049-632x.12193
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of cell mediators and serum cytokines transcript expression between male and female mice infected withMycobacterium aviumsubspeciesparatuberculosisand/or consuming probiotics

Abstract: The gut immune system is complex, and dysregulation leads to a number of disorders including inflammatory bowel syndrome and (in livestock) Johne's disease. Previous work has demonstrated that males and females respond differently to treatment with pathologic and probiotic microorganisms, suggesting that a 'one-size-fits-all' approach to treat GIT inflammation may be inadequate. While we had observed significant differences between males and females in terms of cytokine production, it remains unclear how these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Interestingly, synbiotic treatment induced sex-dependent effects in terms of bacterial abundance mostly following chronic intermittent alcohol intake, and not during basal conditions. Previous preclinical and human studies have documented sex differences both in the baseline profile of gut microbiota, and in the effects of diet and/or probiotic administration in terms of the composition of bacteria and its metabolic products, providing evidence for genotype by diet interactions (65,66). Our data provide evidence for a triple genotype-alcohol-synbiotic interaction on gut microbiota profile.…”
Section: Discussionsupporting
confidence: 64%
“…Interestingly, synbiotic treatment induced sex-dependent effects in terms of bacterial abundance mostly following chronic intermittent alcohol intake, and not during basal conditions. Previous preclinical and human studies have documented sex differences both in the baseline profile of gut microbiota, and in the effects of diet and/or probiotic administration in terms of the composition of bacteria and its metabolic products, providing evidence for genotype by diet interactions (65,66). Our data provide evidence for a triple genotype-alcohol-synbiotic interaction on gut microbiota profile.…”
Section: Discussionsupporting
confidence: 64%
“…Additionally, females responded positively to use lactobacilli when compared to males. The differences observed suggest that male and female gut tissues and microbiota respond to newly introduced microorganisms differently and that gut-associated microorganisms with host immune system responses and metabolic activity are supported by biology distinct to the host sex [ 42 ]. However, further study should be conducted to obtain additional information about the underlying mechanism behind the sex-dependent response of the host animal to treatment with probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The theorized mechanisms by which B. fragilis produces a treatment effect, at least in a mouse model, is through ameliorating enteric microbiome imbalances ( 47 ) including upstream and downstream byproducts which modulate behavior. Other studies not related to ASD have demonstrated that some probiotic strains can influence the immune system ( 48 , 49 ), at least for a certain period of time, and metabolic abnormalities such as redox imbalances ( 50 ).…”
Section: Treatments That May Alter the Gmmentioning
confidence: 99%